Association of platelet and hematocrit value with arteriovenous fistula (AVF) failure in hemodialysis patient at Bali Husada Cipta Canti, Bali, Indonesia - Anak Agung Gede Oka Suta Wicaksana; I Gusti Ngurah Agung Tresna Erawan; Yenny Kandarini (Indonesian Vascular Access Association (IVAA), 2022)
Introduction: Hemodialysis is one of the renal replacement therapies used for end-stage renal disease (ESRD) patients. Arteriovenous fistula (AVF) is the preferred hemodialysis access type because it has better patency rates and fewer complications than other access types. However, around 31-61% of AVF fail to mature. An early AVF failure may be due to a lack of maturation or thrombosis, and late failure defines as a failure after successful use. Some factors that make AVF fail are injury of the endothelial wall or hypercoagulation. This study aimed to determine the association between pre-operative platelet and hematocrit value with AVF failure in BHCC Clinic Denpasar. Method: This is an analytic cross-sectional study. The data were collected from medical records from all dialytic patients from January 2020-December 2020. Patients with inclusion criteria were collected. Patient with incomplete data was excluded. Data were analyzed using Chi-square analysis. Results: Our study involved 34 patients, 21(61.8%) of them were male, and the mean age was 52.62 years (±10.77 SD). The AVF failure prevalence was 32.4% (n=11). We found no association between platelet value with AVF failure, with a p-value=0.411. There was an association between hematocrit value and AVF failure in hemodialysis patients with a p-value=0.032. Most of the patient was male and aged 45-60 with ESRD from the characteristic found. Conclusion: There was an association between pre-operative hematocrit value and AVF failure in hemodialysis patients. There was no association between pre-operative platelet value with AVF failure.